Chemerin, CK, and LDH as Potential Biomarkers for Early Myocardial Infarction Detection: Chemerin, CK, dan LDH sebagai Biomarker Potensial untuk Deteksi Dini Infark Miokard - Mohamed , Wisam Sbhan Khalf (Academia Open, 2025)
General Background: Myocardial infarction (MI) remains a leading cause of mortality worldwide, with early diagnosis being crucial for effective intervention. Specific Background: Biomarkers such as Chemerin, Creatine Kinase (CK), and Lactate Dehydrogenase (LDH) have been implicated in inflammatory responses and vascular dysfunction associated with MI. Knowledge Gap: Despite existing studies on these biomarkers, their combined diagnostic potential and correlation with cardiovascular risk factors remain underexplored. Aims: This study investigates the relationship between Chemerin, CK, and LDH levels in MI patients, alongside other risk factors such as body mass index (BMI) and smoking, to assess their role as potential early diagnostic indicators. Results: A total of 70 samples (50 MI patients, 20 controls) were analyzed at Azadi Educational Hospital, Kirkuk, from November 2023 to March 2024. The study found significantly elevated levels of Chemerin, CK, and LDH (P < 0.05) in MI patients compared to controls, indicating their involvement in inflammation and myocardial damage. Novelty: This study provides evidence that these biomarkers, particularly Chemerin, may serve as predictive indicators for MI risk, offering an alternative approach for early detection. Implications: The findings highlight the potential of biomarker-based screening in clinical settings and emphasize the importance of lifestyle modifications to mitigate MI risks and complications. Highlights: Biomarkers play a crucial role in myocardial infarction diagnosis. Chemerin, CK, and LDH significantly elevated in MI patients (P < 0.05). Potential biomarkers for early MI detection and risk assessment. Keywords: Chemerin; Creatine Kinase; lactate dehydrogenase; Myocardial Infarction; Smoking.